SCOPING REVIEW: APPLICATION OF TACTILE/KINESTHETIC STIMULATION IN PRETERM INFANTS - Juwita, Septiana; Argaheni, Niken Bayu; Alristina, Arie Dwi (Program Studi Kebidanan Fakultas Kedokteran Universitas Sebelas Maret, 2023)
Background: Premature birth is the birth of a baby born less than 37 weeks gestational age with low birth weight are still a major concern in developing countries Low Birth Weight (LBW). That is puts babies at risk not only for neonatal complications, but also for other high-risk factors such as developmental disorders that can be indicated by the baby's physiological and behavioral responses.Objective: To assess the effect of tactile/kinesthetic stimulation on weight gain in preterm infants.Methods: literature search was conducted from the Google Scholar database. Clinical trials studying tactile stimulation or massage therapy in Indonesia whether or not it is related to kinesthetic stimulation of premature infants; who assessed weight gain after the intervention; which has a control group and is compiled in Indonesian. Search results using these keywords yielded 31 articles. Then filtered articles with inclusion and exclusion criteria obtained 24 articles. Selection of the next article by eliminating duplication of articles with the results of 17 articles. Furthermore, the elimination of articles based on a complete arrangement of as many as 4 articles. Of these, meet the inclusion criteria.Result: There are many differences in the application of tactile/kinesthetic stimulation techniques to research. Also, many studies do not describe the side effects that occur during stimulation, the actions taken when the event occurs, and their effect on outcomes.Conclusion: These studies make a relevant contribution to the indications for tactile/kinesthetic stimulation. However, there is no standard for such applications. Future studies should describe the side effects of tactile/kinesthetic stimulation interventions.